Khaki shorts and saffron flags : a critique of the Hindu right - Basu, Tapan (New Delhi : Orient Longman, 1993)
About the Rashtriya Swayam Sevak Sangh, the Vishva Hindu Parishad, and the Hindutva; based on interviews conducted by the authors at various places.
Includes bibliographical references.
Keywords: Rashtriya Swayam Sevak Sangh -- History; Vishva Hindu Parishad -- History; Hinduism and politics -- India; India -- Politics and government -- 20th century